Covid-19 Pandemic: The Effectiveness of Utilizing Micro Business Productive Assistance (BPUM) for MSMEs - Ishak Ishak; Nur Ariani Aqidah; Junastri Junastri (UIN Raden Mas Said Surakarta, 2022)
This study examines the impact of the COVID-19 Pandemic on MSMEs and how the effectiveness of utilizing business capital assistance paid by the government affects their survival during the COVID-19 Pandemic. Through a survey of 110 respondents (namely debtors/beneficiaries), this case study finds that the COVID-19 Pandemic has caused business delays, so the government assistance program has become the key to MSME business continuity during the COVID-19 Pandemic. With government assistance, the business actors in the sample of this study could maintain their business. Even though the overall labor force is decreasing and income is decreasing, some small, medium, and micro-enterprises can maintain or even increase workers and their turnover due to government assistance. This study recommends continuing the assistance program for MSMEs by loosening requirements and focusing on new beneficiaries, an integrated MSME database, and in the future, the assistance program needs to be integrated with financial literacy and MSME innovation programs. The policy implication of this study is that the government's economic recovery plan during the future recession needs to target MSMEs. KEYWORDS: Effectiveness of Utilization, Business Capital Assistance, MSMEs